Greek Livestock Production: Problems and Future Prospectives - Κυριακής Σπ. (Journal of the Hellenic Veterinary Medical Society, 2019)
In this study, the problems and the prospects of the greek livestock production are discussed. It must be pointed out that the annual spendings in foreign exchange exceed 1 billion U.S. dollars in order to cover local needs for livestck products. Proposals are therefore made for a short term, progressive reduction in foreign exchange expenditures as well as for a long term self-powered sufficiency in animal feedstuffs to satisfy our country’s needs.